Solvatochromic Behavior of Dyes with Dimethylamino Electron-Donor and Nitro Electron-Acceptor Groups in Their Molecular Structure - Caroli-Rezende, M; Dominguez-Caru, M (John Wiley and Sons Ltd, 2015)
Six dyes with N,N-dimethylaminophenyl and 4-nitrophenyl or 2,4-dinitrophenyl groups in their molecular structures were prepared and characterized. These compounds have different conjugated bridges (C-C, C-N, and N-N) connecting the electron-donor and the electron-acceptor groups. All compounds are solvatochromic, with reverse solvatochromism occurring. The solvatochromic band observed in each spectrum for the dyes is due to a π rarr π∗ transition, of an intramolecular charge transfer nature, which occurs from the electron-donor N,N-dimethylaminophenyl group to the electron-acceptor group in the molecules, which is reinforced by the structures of the compounds optimized by applying density functional theory, which exhibit high planarity. The reverse solvatochromism was explained considering two resonance structures. The benzenoid form is better stabilized in less polar solvents and characterizes the region displaying positive solvatochromism, while the dipolar form is better stabilized in more polar solvents, in the region of negative solvatochromism. The Catalán multiparametric approach was used to study the contribution of solvent acidity, basicity, dipolarity, and polarizability to the solvatochromism exhibited by the compounds. These compounds are good candidates for the investigation of the polarizability and, to a lesser extent, the dipolarity of the medium, with very little interference from specific interactions of the solvent through hydrogen bonding. Copyright © 2014 John Wiley & Sons, Ltd.